Product market competition and organization capital - Shin, Ilhang; Lee, Hansol (Economics and Business Letters, 2023)
This study examines the impact of product market competition on a firm’s investment in organization capital using a sample of Korean, listed firms during 2001–2020. As the high product market competition provides firms with incentives to build competitive advantages and increase productivity, we hypothesize that increases in product market competition drive firms to invest in organization capital. We found a positive relationship between product market competition and a firm’s investment in organization capital. We also found that such a relationship is more pronounced for firms in the high-tech industry and financially distressed firms.